PERAN PENGGUNAAN INSTAGRAM PERUMDA TIRTA MUSI SEBAGAI MEDIA INFORMASI PELANGGAN - Safrina, Julia Nikita; Nikita Safrina, Julia; Santi Zinaida, Rahma (Jurnal Prodi Ilmu Komunikasi, 2024)
Instagram is a social media that is used by its users as a social resource for sharing information in the form of photos, videos and captions. One of the companies that has Instagram is Perumda Tirta Musi Palembang. With Instagram costumers can easly get information, required in complete and practical manner. The problem identified is the role of using Perumda Tirta Musi’s Instagram as a customer information. Where the data collection technique in this study used observation, documentation and interview data. The data used were analyzed qualitatively. The result in this study indicate that Perumda Tirta Musi Palembang’s Instagram social media provides convenience benefits for providing as well as being a media information for Perumda Tirta Musi’s Customer.